ENT 530 Business Model Canvas: Corndog Crispy Enterprise / Muhamad Rafiqin Razali ... [et al.] - Razali, Muhamad Rafiqin; Mohd Naseri, Natasha Amira; Hamdan, Murni Amiera; Ahmad Zaidi, Puteri Nik Nursyafika; Tuan Mukhtar, Tuan Aimin Syahmie; Zaidi, Nur Khaleeda; Pg Zaidi, Dk Siti Nursyuhada; Anuar, Alia Yasmin; Ungku Zanedreef Shah, Ungku Zanedameral Haleq (2021)
This report is about creating a business model canvas for a simulated business under course of Principles of Entrepreneurship, course coded ENT530. ENT530 is a course under the Faculty of Business Administration and Management. ENT530 is a subject that teaches the principles of entrepreneurship, in which within its syllabus, it teaches the entrepreneurial mindset and decision process that an individual will encounter as the individual pursuing the entrepreneurial opportunities, creating new ventures, and dealing with business management issues. Hence, for this subject, students are expected to analyze issues related to entrepreneurship. Students also are expected to demonstrate leadership and communication skills in preparing a business plan using Business Model Canvas. Furthermore, students are expected to demonstrate entrepreneurial skills in creating a business via a social media. Business Model Canvas (BMC) is a strategic tool for developing new business models or documenting and improving the existing ones. BMC helps a company to align its activities by understanding the potential trade-offs, and understanding own strength, weaknesses, opportunities, and threats. As a great tool, BMC offers focus, flexibility, and transparency besides being easy to tweak, lucid and coherent. Within a single page, it explains the core elements that drive business and omits all unnecessary aspects. For this report, a business named Corndog Crispy is simulated to accomplish the purpose of creating a business model canvas. It is a business that sells corndog through traditional, physical means and beginning to grasp the trend of online sales by inducing an online presence through social media platforms. This process is assisted by a business model canvas that illustrates several aspects such as key partners, key activities, key features, value proposition, customer relationships, channel, customer segments, cost structure, and revenue streams. Hence, suitable examples will be included to demonstrate further the practice of business model canvas. In which it provides understanding on how it shapes the business.